Fatalism: thoughts about tomorrow's sea battle. (19th February 2019) - Cockburn, David
Abstract: The hold of the fatalistic reasoning that Aristotle criticizes is dependent, first, on the idea, articulated by Frege, that the real candidates for truth and falsity are something other than particular contingent happenings such as affirmations or thinkings, and, second, on the idea that the demand for speculative reflection overrides any demand for practical deliberation. Standard challenges to the reasoning embody the same presuppositions and so simply perpetuate the core confusions. They do so most fundamentally in the assumption that we need a 'metaphysical' grounding for our idea of ourselves as agents who have influence on the course of events.